An updated network meta-analysis of EGFR-TKIs and combination therapy in the first-line treatment of advanced EGFR mutation positive non-small cell lung cancer - Qi, Yuexiao; Xia, Xiaojun; Shao, Lihua; Guo, Liyun; Dong, Yumei; Tian, Jinhui; Xu, Lijun; Niu, Ruijun; Wei, Shihong (Frontiers in Oncology, 2022)
Objectives Tyrosine kinase inhibitors (TKIs) are standard care option in patients of non-small cell lung cancer (NSCLC) with epidermal growth factor receptor (EGFR) mutation. TKIs-based combination treatment modes have shown encouraging outcomes. However, it remains unknown which is the optimal treatment as the first-line regimen for these patients on OS. Materials and Methods Randomized controlled trials (RCTs) and meeting abstracts that investigated EGFR-TKIs alone or in combination as front-line care for patients with NSCLC were systematically searched in relevant databases and reviewed. Fixed effects and random effects network meta-analysis model was used to estimate progression-free survival (PFS), overall survival (OS), overall response rate (ORR), and grade 3 and higher adverse events (AEs). Surface under the cumulative ranking curves (SUCRAs) was used to rank treatment effects. Results Eighteen studies covering six treatments and involving a total of 4389 patients were included in this network meta-analysis. On OS, the top 3 treatment were first-generation EGFR-TKIs (1G EGFR-TKIs) plus chemotherapy (SUCRA, 88.1%), osimertinib (SUCRA, 65.8%) and second-generation EGFR-TKIs (2G EGFR-TKIs) (SUCRA, 63.3%). On PFS, the top 3 treatments were osimertinib (SUCRA, 96.0%), 1G EGFR-TKIs plus chemotherapy (SUCRA, 67.1%) and 1G EGFR-TKIs plus antiangiogenesis (SUCRA, 48.2%). Two types of TKI-based combination therapy have significant higher risk of grade 3 and higher adverse events than TKI alone. Conclusion 1G EGFR-TKIs plus chemotherapy and osimertinib seem to be the 2 better options as first-line care in advanced NSCLC patient s with EGFR-mutation. Osimertinib caused the lowest incidence of adverse events. However, TKIs-based combination therapy significantly increased adverse events.